Accelerating Digital Banking Transformation Through User Acceptance: a study on the Millennial Cultural - Arinta, Yusvita Nena; Widyastuti, Emy (Universitas Muhammadiyah Semarang, 2024)
This study aims to examine a conceptual model that explains the main factors that influence the behavioural intention of the millennial generation in their acceptance of the use of digital banking. The conceptual model is based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), with experience as a moderating variable. The modelling was carried out using the Partial Least Square Structural Equation Modeling (PLS-SEM) equation to analyze the data collected from the questionnaires filled out by the respondents. The research results show that behavioural intentions are significantly influenced by performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, and habit. Social influence and price value are not factors that contribute to the cultural behaviour intention of the millennial generation towards accepting the use of digital banking. In line with hypothesis testing, moderation testing with experience as a moderating variable that has no influence is social influence and price value. This study offers the banking sector to design and market products through technological innovation that can become a competitive advantage, thereby increasing the digital banking acceptance of the millennial generation in Central Java.